PENGARUH METODE PEMBELAJARAN GALLERY WALK TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI SISTEM PERTAHANAN TUBUH - Dani Ramdani (Institut Pendidikan Indonesia IPI Garut, 2019)
ABSTRACT The purpose of this study is to determine the influence of Gallery Walk learning method on students' critical thinking ability on body defense system material in class XI SMAN 1 Bantarujeg, Kab. Majalengka.This research was conducted in October 2017 until May 2018. The research method used true experiment method. Population in this research was all class XI IPA SMAN 1 Bantarujeg, Kab. Majalengka as many as 3 classes with the number of students were 104 people. The samples used are 2 classes taken by cluster random sampling that were class XI IPA-1 as experimental class and class XI IPA-2 as control class. Research instrument was critical thinking ability test in the form of description of body defense system material consist of 15 numbers. Technique analysing data used the test of difference of two mean (t-test) with significant level (α) = 5%.Based on the results, the conclusion is that there is influence of GalleryWalk learning method on students' critical thinking ability on body defense system material in class XI SMAN 1 Bantarujeg, Kab. Majalengka, Academic Year 2017/2018. Keywords: gallery walk learning method, critical thinking and body defense system.